2012
DOI: 10.1063/1.3702585
|View full text |Cite
|
Sign up to set email alerts
|

Josephson effect in cuprate superconducting structures

Abstract: Electron transport and microwave properties of cuprate superconducting structures (bicrystal junctions and hybrid mesa heterostructures) are discussed here. Superconducting current in junctions from cuprate superconductors with the dominant dx2−y2-wave symmetry is determined by the barrier properties, characterized by the mid-gap bound states due to the multiple Andreev reflection. In bicrystal junctions it is revealed via linear dependence of critical current density on square root of the transparency, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Extensive experimental work has been performed on studying mesoscopic d-wave superconductor structures (a review of which can be found in [13]). Additional experimental studies have probed current fluctuations and in particular the relation between shot noise and junction bias in mesoscopic d-wave structures [14,15,16]. These shot noise studies find strong agreement with the theoretical predictions derived in [17] which were based the scattering matrix approach.…”
Section: Introductionmentioning
confidence: 55%
“…Extensive experimental work has been performed on studying mesoscopic d-wave superconductor structures (a review of which can be found in [13]). Additional experimental studies have probed current fluctuations and in particular the relation between shot noise and junction bias in mesoscopic d-wave structures [14,15,16]. These shot noise studies find strong agreement with the theoretical predictions derived in [17] which were based the scattering matrix approach.…”
Section: Introductionmentioning
confidence: 55%
“…along the crystal c axis. Such a situation is realized, e.g., in mesas [52][53][54][55][56][57]. In this case, tunneling is predominantly incoherent [9], and it was considered by us earlier [58][59][60][61] with the special emphasis on the possible influence of the charge density wave (CDW) manifestations.…”
Section: Introductionmentioning
confidence: 99%